Acetate‐utilizing bacteria at an oxic–anoxic interface in the Baltic Sea. Issue 2 (15th April 2013) - Berg, Carlo; Beckmann, Sabrina; Jost, Günter; Labrenz, Matthias; Jürgens, Klaus
Abstract: Pelagic redoxclines represent chemical gradients of elevated microbial activities. While chemolithoautotrophic microorganisms in these systems are well known as catalysts of major biogeochemical cycles, comparable knowledge on heterotrophic organisms is scarce. Thus, in this study, identity and biogeochemical involvement of active heterotrophs were investigated in stimulation experiments and activity measurements based on samples collected from pelagic redoxclines of the central Baltic Sea in 2005 and 2009. In the 2009 samples, 13 C‐acetate 16S rRNA stable isotope probing (16S rRNA‐SIP) identified gammaproteobacteria affiliated with Colwellia sp. and Neptunomonas sp. in addition to epsilonproteobacteria related to Arcobacter spp. as active heterotrophs at the oxic–anoxic interface layer. Incubations from sulfidic waters were dominated by two phylogenetic subgroups of Arcobacter . In the 2005 samples, organics, manganese(IV), and iron(III) were added to the sulfidic waters, followed by the determination of metal reduction and identification of the stimulated organisms. Here, the same Arcobacter and Colwellia subgroups were stimulated as in 2009, with Arcobacter predominating in samples, in which manganese(IV) reduction was highest. Our results offer new insights into the heterotrophic bacterial assemblage of Baltic Sea pelagic redoxclines and suggest Arcobacter spp. as a heterotroph with presumed relevance also for manganese cycling.